Structure and characteristics of boron-containing steels for fasteners - H. P. Haretski; N. f Solovey; S. L. Shenets; A. V. Tereshchenko; S. V. Avdeev; A. I. Pokrovskii; O. I. Tolkacheva (Литьë и металлургия, 2020)
According to TU 14-1-4486-88 and TU 14-1-5490-2004, in accordance with international standards DIN EN 10263-4, OJSC «BSW – Management Company of the Holding «BMC» produces hot-rolled products of the following grades of steel: 20Г2Р, 30Г1Р, 20MnB4, 30MnB4 and 32CrB4 microalloyed with boron. They are used for the manufacture of fasteners instead of previously used steels 35X, 38X and 40X. The use of boron-containing steels reduces the surface defects of hardware; to increase the stability of the mechanical properties of bolts, screws, studs, strength class 8.8 and 10.9 by GOST 1759.4-87; to achieve a high level of toughness at negative temperatures. It is shown that steel 20Г2Р provides stable mechanical properties of products up to M27 (in contrast to steel grades 35X, which are designed exclusively for bolts of class M16 8.8). The boron-containing steels in the delivery state with the structure of granular perlite have high technological plasticity – in the cold, the bolt head is formed and the thread is rolled without tearing in the thread hollows, as is the case with chromium steels of type 40X. It was found that their ductility increases due to the low content of carbon and chromium, as well as the formation of dispersed carbonitride-boride phases of a globular form.